Fifth Festival Concert by the Vienna Philharmonic at the Salzburg Festival, Sunday, August 11, 1938, in the Mozarteum - Wiener Philharmoniker::::::::::::::: (R. Kiesel; Austria; Salzburg, 2020)
Program for a performance by the Vienna Philharmonic under the direction of Karl Böhm, including Beethoven's Fifth Symphony, and works by C.M. von Weber and Mozart.